2023
DOI: 10.1021/acs.energyfuels.2c03636
|View full text |Cite
|
Sign up to set email alerts
|

Quantification of Amines in Refinery Process Water via Surface-Enhanced Raman Spectroscopy

Abstract: Amines are used in crude oil production, natural gas recovery, and hydrocarbon refining as hydrogen sulfide scavengers, corrosion inhibitors, and pH control neutralizers. Residual amines can be detrimental to the refining process, such as forming heat-stable salts that lead to corrosion-inducing deposits or causing nitrification of wastewater streams. Traditional methods for amine analysis such as ion chromatography are complex, time-consuming, and not adapted to field deployment. We present a new method using… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 24 publications
0
4
0
Order By: Relevance
“…Herein, the detection of pharmaceuticals, personal care products (PCP), and heavy ions in water treatment is introduced (see Table 2). We begin with the detection of pharmaceuticals and PCP [69][70][71][72][73][74][75][76][77][78][79], and we end with those of heavy ions [80][81][82][83][84].…”
Section: Detection Of Pharmaceuticals Personal Care Products and Heav...mentioning
confidence: 99%
See 2 more Smart Citations
“…Herein, the detection of pharmaceuticals, personal care products (PCP), and heavy ions in water treatment is introduced (see Table 2). We begin with the detection of pharmaceuticals and PCP [69][70][71][72][73][74][75][76][77][78][79], and we end with those of heavy ions [80][81][82][83][84].…”
Section: Detection Of Pharmaceuticals Personal Care Products and Heav...mentioning
confidence: 99%
“…This was assessed at 10 mg/L for CMIT molecules in lake water [72]. By another strategy, Benhabib et al showed the SERS detection of the monoethanolamine (MEA) in the water of the refinery process [73]. In this study, the authors employed gold nanoparticles for enhancing the SERS signal, but also an internal standard, which is an isotopologue of MEA, which is structurally identical, but can be distinguished in a spectroscopic manner (see Figure 5a).…”
Section: Detection Of Pharmaceuticals Personal Care Products and Heav...mentioning
confidence: 99%
See 1 more Smart Citation
“…20 The method proved to be very useful for the quality control of triazinebased commercial H 2 S scavengers and the quantification of residual reactants during the scavenging process. On the other hand, a recent study showed the possibility of detecting ppm levels of amines in refinery wastewaters using the ultrasensitive surface-enhanced Raman spectroscopy (SERS) technique, 21 laying the groundwork for the detection of ultralow levels of substituted 1,3,5-triazines or other known nitrogen-containing H 2 S scavengers in downstream processes. Despite the increased use of Raman spectroscopy in H 2 S removal processes, its application in the field of thiol scavengers has been very limited.…”
Section: ■ Introductionmentioning
confidence: 99%